Pemberdayaan Masyarakat Kampung Sayur Perkotaan Menjadi Kampung Wisata Berbasis Edukasi Melalui Implementasi Urban Farming - Ester Nurhana Kusumawati; Roynerd Vhiranda Katanga T; Herlin Mienantha Simbiak; lisabeth Lelu Lagamakin; Augita Tri Clara Shostakovich D.R; Ricky Nopandra Sembiring; Aquilinus Royen; Oktovilla Delia Saflembolo; Effie Rambu Boba; Nicodymus Pramudya Dyan K; Agustina Tri Mulyani; Farman D Larono; Glori Andrew S; Laurensia Christina A.N; Yose Hendri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
During the current Covid-19 pandemic, there are many problems that occur in various sectors such as tourism and food. To achieve food security during a pandemic, urban farming is one of the most appropriate options to implement. Besides being easy, urban farming has its own potential and attractiveness if it is developed into tourism. Visitors will be able to see and learn firsthand the hydroponic farming process from the beginning to processing harvested products. The location of this project is in Bausasran Village, Danurejan District, DIY. In its implementation, urban farming activities do not only focus on economic and ecological values ​​but also on educational values. The method of service activities is carried out online and offline to reduce the risk of the spread of Covid-19 so as to maximize agricultural potential, and improve the welfare of the residents of Kampung Sayur Bausasran and realize the village's ideals as an education-based tourism village. Various activities have been carried out and resulted in physical and non-physical changes in the target communities, including: 1) the establishment of a building and a nursery management system used by the local community as a location for seed cultivation, (2) training which includes training in the manufacture of liquid fertilizer from organic materials, training on fish farming in buckets, training on the manufacture of processed agricultural products from each farmer group and training on financial management and organizational.